2009
DOI: 10.1111/j.1440-1789.2009.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathy of an infiltrating monocyte lineage during the early phase of infection with murinecoronavirus in the brain

Abstract: Viral spread during the early stages after infection was compared between a highly neurovirulent mouse hepatitis virus (MHV), JHMV cl-2 strain (cl-2), and its low-virulent mutant, soluble-receptor-resistant (srr)7. The infection of cells with srr7 (soluble-receptor-resistant mutant 7) is dependent on a known MHV receptor (MHVR), carcinoembryonic cell adhesion molecule 1a, whereas cl-2 shows MHVR-independent infection. Initial viral antigens were detected between 12 and 24 h post-inoculation (p.i) in the infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 44 publications
4
42
0
Order By: Relevance
“…Neuropathological imaging after infection with srr7 and cl-2 showed that srr7 induced lesions in the cerebral white matter without infecting neurons, which do not express carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM-1), a major MHV receptor (MHVR). In contrast, cl-2 causes necrosis primarily in the gray matter by infecting neurons in an MHVR-independent manner (1,3). The MHVR-dependency and -independency of srr7 and cl-2 infections, or of other JHMV strains, cause in vitro infections of BHK cells, which are MHVR-negative (4-7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathological imaging after infection with srr7 and cl-2 showed that srr7 induced lesions in the cerebral white matter without infecting neurons, which do not express carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM-1), a major MHV receptor (MHVR). In contrast, cl-2 causes necrosis primarily in the gray matter by infecting neurons in an MHVR-independent manner (1,3). The MHVR-dependency and -independency of srr7 and cl-2 infections, or of other JHMV strains, cause in vitro infections of BHK cells, which are MHVR-negative (4-7).…”
Section: Introductionmentioning
confidence: 99%
“…These differences in neuropathogenesis and MHVR-dependency between srr7 and cl-2 are attributed to a single mutation in the S2 gene (2) within the S protein-encoding region (S gene). The S gene has a high mutation rate (8) and we have obtained several mutant viruses after re-cloning of an srr7 viral stock (maintained in our laboratory for over 10 years) through repeated passages (3,7). All of the isolated mutant viruses (Br-1, Mu-1, and Mu-2) had single or double amino acid substitutions in the S protein, which, compared with the maternal srr7, helped them gain increased virulence and an MHVR-independent manner of infection (7).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that most of the syncytia formed after infection of TGPECs expressed Gr-1 antigen. The main target among leukocytes of MHV-JHM infection has been believed to be the lineages of Mo/Mas, including microglia in the brain (5,29), which express CEACAM1. CEACAM1 is also detectable as an adhesion molecule on Gr-1-positive human granulocytes (22).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it produces necrotic lesions in the grey matter with infected neurons, which do not express the major MHV receptor carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) (3,4). A mutant clone isolated from cl-2, srr7, shows attenuated neurovirulence compared to cl-2, although its virulence is still higher than that of the other JHMs, exhibiting rapid viral spread from one organ to another non-adjacent organ within 12 hours after infection, designated as super-acute spread (5). Most of the mice infected with srr7 survive for more than 7 days and die within 10 dpi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation